Transient control of gasoline engines - Shen, Tielong (CRC Press, 2016)
Transient Control of Gasoline Engines drives to move progress forward. A stimulating examination of car electronics and digital processing technology, this book chronicles significant advances that have occurred over the past 20 years (including the change from combustion engines to computerized machines) and presents new and exciting ways to enhance engine efficiency using real-time control technology. Dedicated to improving the emissions of automotive powertrains, it provides an introduction to modeling, control design, and test bench, and explains the fundamentals of modeling and control design for engine transient operation. It also presents a model-based transient control design methodology from the perspective of the dynamical system control theory. Written with graduate students in mind, this book: Addresses issues relevant to transient operation, cycle-to-cycle transient, and cylinder-to-cylinder balancing Examines the real-time optimizing control problem (receding horizon optimization, for torque tracking control and speed control) Covers three benchmark problems related to the modeling and control of gasoline engines: engine start control, identification of the engines, and the boundary modeling and extreme condition control Transient Control of Gasoline Engines describes the behavior of engine dynamics operated at transient mode as a dynamical system and employs the advanced control theory to design a real-time control strategy that can be used to improve efficiency and emission performance overall. Geared toward graduate students, this book also serves as a trusted source for researchers and practitioners focused on engine and engine electronics design, car electronics, and control engineering.
Includes bibliographical references (pages 277-287). - Online resource; title from PDF title page (EBSCO, viewed November 2, 2015)
Keywords: Automobiles -- Electronic equipment; Automobiles -- Motors -- Computer control systems; Automobiles; Équipement électronique; Automobiles; Moteurs; Commande par ordinateur; TECHNOLOGY & ENGINEERING; Engineering (General); Automobiles; Electronic equipment; Automobiles; Motors; Computer control systems